O ambiente acadêmico e acessibilidade arquitetônica: estudo de caso, Universidade Federal Rural do Semi-Árido, Pau dos Ferros-RN - Paiva, Ruana Rafaela Batista (Universidade Federal Rural do Semi-Árido, 2017)
This paper is the result of a critical, bibliographical and experimental analysis undertaken in the infrastructure of the Federal Rural University of the Semi-Arid (UFERSA), Campus Pau dos Ferros, regarding architectural accessibility. The aim is to analyze the irregularities found in the institution related to architectural barriers. The methodology of this study was based on the conceptual references of the regulatory norms, pertinent authors to the research area, which emphasize the importance and urgency on the issues for the right to come and go of disabled person in the perspective of the conquest of citizenship and social inclusion. In addition, explaining the implementation of the universal design as a main part of the project. The field trip provided the main subsidies for the results. Around the campus, regarding the areas with high flow of people, such as the administrative building, classrooms and professor's offices, main hall and laboratories, it was possible to observe some inefficiencies related to the availability of accessible spaces, such as deteriorated sidewalks and ramps, as well as inappropriate emergency exits. In conclusion, it is understood the need for both physical and social inclusive practices in the form of inclusion of everybody in the academic environment, providing for both the university public and the employees of the multidisciplinary center safe mobility and comfort around the campus.
The academic environment and architectural accessibility: case study, Federal Rural University of the Semi-Arid, Pau dos Ferros-RN
Keywords: Acessibilidade; Ambiente acadêmico; Inclusão social; Accessibility; Academic environment; Social inclusion; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA